Femtosecond x-ray induced fragmentation of Ho3N@C80. (August 2015) - Xiong, H; Murphy, B; Fang, L; Osipov, T; Kukk, E; Guehr, M; Feifel, R; Petrovic, V S; Ferguson, K R; Bozek, J D; Bostedt, C; Frasinski, L J; et al.
Synopsis: We report on new data regarding on the photoionization and fragmentation dynamics of gas phase endohedral fullerenes Ho3 N@C80 obtained with intense femtosecond X-ray pulses from the Linac Coherent Light Source (LCLS) free electron laser (FEL).